2021
DOI: 10.1504/ijsmm.2021.118823
|View full text |Cite
|
Sign up to set email alerts
|

Winning the loyalty cup: impact of symbol-related brand elements on brand loyalty of sports clubs

Abstract: Extant research in marketing has recognized the importance of branding in sports.Professional sports clubs are considered to be big brands, and fan loyalty is a crucial factor in determining their success. Brand elements are the building blocks of brands and are used by brand managers to create distinct associations in consumers' minds, resulting in brand recall and recognition. This study employs the context of football to explore the relationship between the symbol-related brand elements of a sports club and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Logo is a primary element in corporate visual identity, playing a crucial role in expressing an organization. Previous research has extensively examined the cognitive and perceptual aspects of logos, including their impact on consumer behavior and business purchasing decisions (Shi & Jiang, 2023;Reghunathan & Joseph, 2021;Rafiq et al, 2020). This study not only supplements past research on cognition and perception but also extends the understanding of the influence of logos on customer purchase motivation, providing further insights into the impact on consumer purchasing behavior.…”
Section: Conclusion and Significancementioning
confidence: 52%
See 1 more Smart Citation
“…Logo is a primary element in corporate visual identity, playing a crucial role in expressing an organization. Previous research has extensively examined the cognitive and perceptual aspects of logos, including their impact on consumer behavior and business purchasing decisions (Shi & Jiang, 2023;Reghunathan & Joseph, 2021;Rafiq et al, 2020). This study not only supplements past research on cognition and perception but also extends the understanding of the influence of logos on customer purchase motivation, providing further insights into the impact on consumer purchasing behavior.…”
Section: Conclusion and Significancementioning
confidence: 52%
“…A positive brand attitude, a favorable brand image, and a positive purchasing experience will further foster customer loyalty, leading to sustained consumer behavior. Reghunathan and Joseph (2021) investigated the relationship between sports club brand elements and customer loyalty. They found that club history, jerseys, and logos related to the brand positively influence consumer brand loyalty.…”
Section: Logos and Customer Loyaltymentioning
confidence: 99%